Aplicação do método do custeio TDABC para determinar os custos dos subprocessos de almoxarifado: um estudo de caso em uma instituição de ensino superior - Oliveira, Euzébio Dia de (2024)
Cost information systems in public agencies are configured as important governance instruments, contributing to the most varied management processes, providing transparency in the application of resources, subsidizing decision-making, and promoting financial sustainability. However, implementing cost information systems in Higher Education Institutions (HEIs) is a complex task, requiring a simplified methodology, through which the costs for implementing and updating the model are not higher than the benefits generated. In this context, considering the recommendations of NBC TSP n.º 34/2021, the Time-Driven Activity-Based Costing (TDABC) costing method presents itself as an alternative to be evaluated for the generation and improvement of the granularity of cost information. Therefore, this study aims to analyze the use of the TDABC costing method to determine the costs of UNILA's subprocesses, based on its pilot application in the Storeroom Section, to provide the institution with information on the data and procedures necessary for its adoption. Thus, this is an applied case study, with qualitative and descriptive approach. The TDABC method was implemented according to the phases proposed by Kaplan and Anderson (2007): Preparation; Analysis; and Construction of the Pilot Model. Throughout these phases, the main difficulty observed was the determination of standard times, especially for more complex activities, where there is no standard or uniformity of tasks performed, due to the characteristics of the demands met. This difficulty may have contributed to the significant percentage variations identified between the estimated costs through the standard time and the costs determined from the collected times. However, the incidence of bias in the collection of times through selfobservation cannot be ruled out. Despite this, the results demonstrated that TDABC offers a range of relevant information, such as the identification of activities and subprocesses that consume more resources, allowing the analysis of potential inefficiencies, which can contribute to the improvement of procedures performed; revelation of the costs of organizational units subordinate to macro-units, information previously unknown; insight into the amount of time teams are available to perform activities; and generation of the Cost Capacity Rate (CCR), which can be applied not only in the calculation of intermediate and final object costs but also in scenario simulations, allowing the analysis of the budgetary impact of planned actions. Finally, the procedures used, and the results obtained, in addition to enabling learning about the implementation of the method, allowed the calculation of the costs of the SEAL sub-processes, demonstrating the TDABC's ability to improve the granularity of cost information. Besides in addition to providing information that allows managers to evaluate the feasibility of generalizing the model at the institutional level, this research contributes to academic discussions and assists other public agencies that intend to implement or improve their cost information systems.